Experimental study on the determination of welding residual stress in rib-deck weld by sharp indentation testing. (April 2021) - Wang, Qiudong; Ji, Bohai; Fu, Zhongqiu; Xu, Zhaodong
Abstract: Implementing accurate fatigue evaluation of rib-deck welds in orthotropic steel decks (OSDs) has become a focus in recent years. In light of the considerable effect of the welding residual stress (WRS), the surface WRS at weld toe or root (i.e., potential crack initiation position) should be accurately determined, which is a challengeable task. In this study, an evaluation framework combining the sharp indentation testing and finite element analysis (FEA) was proposed. Experimental works on the determination of crack initiation position on a microscale, microhardness and WRS, as well as the numerical work simulating welding process, were carried out. The measured WRS was also compared with the values determined by the hole-drilling method. Results show that the proposed evaluation framework is feasible to determine the surface WRS at weld toe and root. The weld root crack usually initiates at the heat affected zone (HAZ), while the weld toe crack initiates at either the weld metal (WM) or the HAZ. Accordingly, both microhardness and WRS at the potential crack initiation positions are presented and discussed. The results are of importance for accurately evaluating the fatigue durability of rib-deck welds. Highlights: An evaluation framework is proposed to determine the surface WRS. Crack initiation position is investigated by metallographic analysis. Microhardness in WM, HAZ and BM of a rib-deck weld is presented. Surface WRS is evaluated using the proposed framework.